2010
DOI: 10.1093/brain/awq217
|View full text |Cite
|
Sign up to set email alerts
|

Blocking ADAM10 synaptic trafficking generates a model of sporadic Alzheimer’s disease

Abstract: We describe here an innovative, non-transgenic animal model of Alzheimer's disease. This model mimics early stages of sporadic disease, which represents the vast majority of cases. The model was obtained by interfering with the complex between a disintegrin and metalloproteinase domain containing protein 10 (ADAM10), the main α-secretase candidate, and its partner, synapse-associated protein 97, a protein of the postsynaptic density-membrane associated guanylate kinase family. Association of ADAM10 with synaps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 52 publications
0
46
0
Order By: Relevance
“…The interaction involves the SH3 domain of SAP97 and an atypical proline-rich domain within the C-terminal region of ADAM10, and favours the forward trafficking of ADAM10 and its localization in synaptic membranes and, thereby, its APP-cleaving activity (12). The ADAM10/SAP97 interaction has been shown to be reduced in brains from AD patients (15), and the disruption of the association between SAP97 and ADAM10 in vivo using peptides leads to the generation of a nontransgenic model of the disease (16). Thus, forward trafficking and membrane insertion are crucial not only for maintaining a pool of ADAM10 at synaptic sites and for ADAM10-shedding activity, but also for healthy neuronal function.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction involves the SH3 domain of SAP97 and an atypical proline-rich domain within the C-terminal region of ADAM10, and favours the forward trafficking of ADAM10 and its localization in synaptic membranes and, thereby, its APP-cleaving activity (12). The ADAM10/SAP97 interaction has been shown to be reduced in brains from AD patients (15), and the disruption of the association between SAP97 and ADAM10 in vivo using peptides leads to the generation of a nontransgenic model of the disease (16). Thus, forward trafficking and membrane insertion are crucial not only for maintaining a pool of ADAM10 at synaptic sites and for ADAM10-shedding activity, but also for healthy neuronal function.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, ADAM10 is the primary endogenous ␣-secretase (Jorissen et al, 2010;Kuhn et al, 2010). Evidence from both AD mouse models and AD human patients suggests the involvement of ADAM10 in the regulation of AD pathogenesis (Epis et al, 2010;Kim et al, 2010). In addition to APP processing, ADAM10 is involved in the shedding of many other biologically important proteins (e.g., Notch, N-cadherin, and Nectin-1) from cell membranes (Hartmann et al, 2002;Uemura et al, 2007;Kim et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The activity of ADAM10 is regulated by NMDA receptors (NMDARs), which modulate synaptic trafficking of ADAM10 via synapse-associated protein-97 (SAP97) (Marcello et al, 2007). Interference of the interaction between ADAM10 and SAP97 causes sporadic AD (Epis et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, ADAM10 has emerged as the constitutive and inducible APP α-secretase in neurons (5). Of note, ADAM9 and ADAM17 do not recover α-secretase proteolysis of APP in the absence of ADAM10 (5), neuron-specific overexpression of ADAM10 decreases Aβ load in a mouse model of AD (6), and impaired ADAM10 trafficking to the synapse generates a model of sporadic AD (7). Similarly, human studies have observed deficits in ADAM10 expression (8), trafficking (9), and activity (10) in AD.…”
mentioning
confidence: 99%